Mortality, bone density and grip strength: lessons from the past and hope for the future? - Westbury, LD; Laskou, F; Patel, HP; Cooper, C; Dennison, EM (Oxford University Press, 2024)
Lay Summary: What does this mean for patients? Low grip strength is important in the diagnosis of sarcopenia (loss of muscle mass and strength with age) and low bone density is used to define osteoporosis. Both sarcopenia and osteoporosis are common conditions among older people and are related to increased risk of poor health. In this study we examined grip strength and bone density in relation to the risk of death using data from older UK men and women from the Hertfordshire Cohort Study (aged 59–73 years at the start of the study). Lower grip strength was related to an increased risk of death (any cause) and death due to cardiovascular causes. In contrast, the relationships between bone density and risk of death (any cause) and death due to cardiovascular causes were weak. Relationships between muscle strength and risk of death were much stronger than the relationships between bone density and risk of death. This may reflect better treatment of low bone density, compared with low muscle strength, in this group of older people. This suggests that advances in the treatment of low muscle strength are required.